PLURALISME AGAMA MENURUT PERSPEKTIF DOSEN-DOSEN FAKULTAS USHULUDDIN DAN HUMANIORA DAN STT GEREJA KALIMANTAN EVANGELIS (GKE) BANJARMASIN - Karianto, Slamet (Jurnal Studia Insania, 2015)
This script writing against the background of social conditions in South Kalimantan diverse in terms of ethnicity, or religion. We take the example of religious pluralism in South Kalimantan. This religious pluralism condition often we term Religious Pluralism. Religious Pluralism succession plays a very important to maintain the diversity and creating understanding of the harmony that lately in various areas, especially in Indonesia being tested. Religious pluralism is a perspective of religious harmony. This understanding of the role in order to be more effective is to educate every student either by teachers, lecturers and other teaching staff in order to achieve that purpose. Both from the Primary Education, Secondary, to university, both from High school and College of General. Results of field interviews showed that religious pluralism is understood by some of the Faculty of Islamic Theology and Humanities IAIN Antasari is a pluralism that if no further interpreted it leads to liberalism even to relativism and nihilism. However, if seen from what has been interpreted by some leaders of Religious Pluralism, then pluralism itself be accepted as a philosophy in building harmony. While others say that sociologically Religious Pluralism has to be accepted by Muslims without having interpreted the deeper, because Pluralism itself is not relativism, or even nihilism. Meanwhile, partially-Lecturer Lecturer STT Borneo Evangelical Church (GKE) views of Religious Pluralism in context pluralistic society will be criticized for some faiths who are intolerant of other religions. While others consider only limited Religious Pluralism understand the differences and cooperation in specific social issues, without any compromise in theology, leading to the elimination of the role of God in life.